1999
DOI: 10.1002/(sici)1097-0231(19991030)13:20<2014::aid-rcm748>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

Polyamine co-matrices for matrix-assisted laser desorption/Ionization mass spectrometry of oligonucleotides

Abstract: The analysis of oligonucleotides using matrix-assisted laser desorption/ionization mass spectrometry (MALDI-MS) has led to the investigation of the use of matrix additives (i.e., co-matrices) to help improve the poor spectral quality commonly observed during the analysis of this class of compounds. The use of certain matrix additives in MALDI-MS has been investigated previously, and these additives have been shown to enhance the desorption/ionization efficiency of oligonucleotides during the MALDI experiment. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
19
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 30 publications
0
19
0
Order By: Relevance
“…Matrix‐assisted laser desorption/ionization mass spectrometry (MALDI‐MS) is relatively well established in small molecule analysis with examples of detection and characterization of lipids, drugs, carbohydrates, and oligonucleotides . The analysis of lipids by MALDI has been a topic of much recent interest and the technique has been used to identify lipid biomarkers in diseases such as Fabry disease, Tay Sachs/Sandhoff, and cancers .…”
mentioning
confidence: 99%
“…Matrix‐assisted laser desorption/ionization mass spectrometry (MALDI‐MS) is relatively well established in small molecule analysis with examples of detection and characterization of lipids, drugs, carbohydrates, and oligonucleotides . The analysis of lipids by MALDI has been a topic of much recent interest and the technique has been used to identify lipid biomarkers in diseases such as Fabry disease, Tay Sachs/Sandhoff, and cancers .…”
mentioning
confidence: 99%
“…The only observations of natural polyamineoligonucleotide complexes by mass spectrometry have been reported in the case where spermine was used as matrix additives for oligonucleotide analysis by MALDI-TOF [12][13][14][15]. In this case, protonated sites of the polyamine were expected to bond DNA phosphate in solution to displace alkaline cations [12][13][14] and stabilize duplexes [15]. Ideally, polyamine protons were transferred to DNA phosphates during sample crystallization or desorption/ ionization process and the oligonucleotide free of alkaline cation and polyamine was observed.…”
mentioning
confidence: 99%
“…Pieles et al [21] showed that the addition of diammonium hydrogen citrate to a trihydroxyacetophenone matrix is an effective combination for reducing cation adducts and improving ion production of the oligodeoxynucleotides. Limbach et al [22][23][24] examined organic base co-matrices such as triethylamine, imidazole, piperidine, and polyamine. It was thought that these additives reduced the cation adduction problem and improved the gas-phase stability of the oligodeoxynucleotides.…”
mentioning
confidence: 99%